Religiously Disaffiliated, Religiously Indifferent, or Believers without Religion? Morphology of the Unaffiliated in Argentina - Esquivel, Juan (Religions, 2021)
This article aims to characterize the socioeconomic and demographic profile of the population without religious affiliation in Argentina as well as their beliefs, practices, and attitudes toward a range of issues related to public and private life. This is a social conglomerate that has grown exponentially in the region and worldwide, but it has been little explored by the social sciences of religion in Latin America. The research was based on the Second National Survey on Religious Beliefs and Attitudes in Argentina, which was carried out in 2019. The study universe was made up of the population of the Argentine Republic aged 18 years or more, living in localities or urban agglomerations with at least 5000 inhabitants. A total of 2421 cases were selected through a multistage sampling. The analysis of the data reveals that it would be inaccurate to say that the religiously unaffiliated do not convey religious beliefs. Almost three out of 10 (most of those who responded do not belong to any religion but neither defined themselves as agnostics or atheists) believe in God and in Jesus Christ. Given that they are the most numerous sub-group and with the highest growth rate within the religiously unaffiliated, it would be unwise to consider this fringe of the Argentine citizenry as a-religious. Nor can we unify them under the category of disaffiliates. Although six out of 10 have a history identified with some religion (and in those cases, it is indeed possible to observe a process of religious disaffiliation), the remaining 40% show paths defined by the alienation from the institutionalized religious spaces since their earliest age.